Circularly-polarized-pulse-driven ultrafast optical currents in monolayer hexagonal Boron Nitride (h-BN) - Hewageegana, P.; Apalkov, V. (Solid State Communications, 2022)
We predict the fundamentally fastest, ultrafast optical currents in monolayer hexagonal Boron Nitride (h-BN) by a circularly-polarized single-oscillation optical pulse. The femtosecond currents in gapped graphene and transition metal dichalcogenides have been discussed. However, the extension of the gapped graphene model for the large bandgap () has not been shown before. The strong optical pulse redistributes electrons between the bands and generates femtosecond currents during the pulse. The pulse generates both direction and direction currents due to charge transfer through the system. Thus, femtosecond ultrashort laser pulses provide an effective tool to manipulate and study the transport properties of electron systems and enhance the conductivity in solids at an ultrafast time scale with high temporal resolution. Ultrafast currents and charge transfer in monolayer h-BN may provide a fundamental basis for petahertz-band information processing.
Keywords: Ultrafast optics Hexagonal Boron Nitride Topological resonance Optical currents Transferred charge